Evaluasi Pengembangan Keprofesian Berkelanjutan Dalam Peningkatan Kompetensi Profesional Pendidik - Yohamintin Yohamintin; Johar Permana; Diding Nurdin; Suharjuddin Suharjuddin; Ahmad Hafidh Alkaf; Yayah Huliatunisa (Universitas Kristen Satya Wacana, 2021)
Continuing Professional Development Program has not received a good response. Elementary school teachers are still not optimal in carrying out research, self-development, creating innovative works, and scientific publications. This study evaluates the professional development program in terms of the principal's role in improving the professional competence of teachers; and to evaluate the process of continuous professional development in improving the professional competence of educators. This study uses a qualitative descriptive approach with a case study design. The subject of this research is the principal and the teacher who teaches at the school. The results showed: 1) that the majority of teachers did not have a structured plan; 2) Implementation of class action research is still low; 3) The development of innovation works to support learning is still low; 4) Implementation of self-development by attending scientific activities on a medium scale; 5) Implementation of scientific paper publications is still very low; 6) Policy support is needed to hold continuous professional development training programs on an ongoing basis; 7) the role of the principal is needed in supervising teacher performance and improving professional competence. In contrast to previous research, this research raises the problems faced by schools with the evaluation of the professional development program and shows the impact and also solutions that can be taken by schools in an effort to improve school quality.